Interest of the Addition of Taxanes to Standard Treatment in First-Line Advanced HER2 Positive Gastroesophageal Adenocarcinoma in Selective Patients - Orillard, Emeline; Henriques, Julie; Vernerey, Dewi; Almotlak, Hamadi; Calcagno, Fabien; Fein, Francine; Fratté, Serge; Jary, Marine; Klajer, Elodie; Vienot, Angelique; Borg, Christophe; Kim, Stefano (Frontiers in Oncology, 2022)
Background Studies have reported a beneficial role of the addition of trastuzumab to platin-5-FU based chemotherapy in first-line advanced HER2 positive gastroesophageal adenocarcinoma (GEA). However, the effect of taxanes combined with platin-5FU + trastuzumab (PFT) is understudied. Methods We performed a retrospective cohort study to evaluate the interest of taxanes among HER2-positive advanced GEA patients treated with PFT. We enrolled HER2-positive advanced GEA patients who underwent treatment between January 2009 to March 2021 in seven hospitals centers in France, treated with PFT alone (S group) or with taxanes + PFT regimen (T group). The primary outcome was progression-free survival (PFS). Also, overall survival (OS), response rate, conversion surgery rate and safety were evaluated. Results Overall, 65 patients received PFT-based therapy, 24 patients in the T group and 41 patients in the S group. To avoid the selection bias, only those patients presenting an ECOG-PS of 0-1 and synchronous metastasis (21 patients in the T group and 19 patients in the S group) were included for analysis. The median PFS was 9.3 months (95%CI 7.0 to 17.2) in the T group and 5.9 months (95%CI 3.7 to 9.6) in the S group (log-rank p=0.038). Treatment by taxanes was significantly associated with a better PFS in univariate (HR 0.49; 95%CI 0.25 to 0.98, p=0.042) and multivariate Cox regression analysis (HR 0.44; 95%CI 0.21 to 0.94, p=0.033), and IPTW method (HR 0.56; 95% CI 0.34 to 0.91, p=0.019). OS was prolonged (19.0 months (95%CI 7.8 to 45.2) vs 13.0 months (95%CI 5.5 to 14.8), log-rank p=0.033) in favor of T group. Treatment by taxanes was significantly associated with a better OS in univariate Cox regression analysis (HR 0.49; 95%CI 0.21 to 0.96, p=0.038) and IPTW method (HR 0.49; 95% CI 0.29 to 0.84, p=0.009). The response rate was higher in the T group, with conversion surgery in five patients. No treatment-related death was observed in both groups. Conclusions Given the improvement in PFS and OS, the addition of a taxanes to standard chemotherapy could be considered as a promising treatment for selected HER2-positive advanced GEA patients, with PS 0-1 and synchronous metastasis (NCT04920747).